Pengaruh Pembelajaran Literasi Numerasi Terhadap Hasil Belajar Matematika Peserta Didik - Harianti Harianti; Cayati Cayati; A. Alfiani Damayanti; Jusmawati Jusmawati (Lembaga Bale Literasi, 2023)
This study aims to determine the effect of literacy learning numeracy on the mathematics learning outcomes of class IV students at UPT SPF SD Inpres Antang I Makassar. This study used quantitative research with the type of pre-experimental research in one group pretest-posttest. The sample used was class IVB students as many as 31 students consisting of 9 men and 22 female. Technique sampling used purposive sampling technique. Instrument research used was the observation sheet, test results and learning documentation. Data were analysed using descriptive statistical analysis and analysis inferential statistics with the help of SPSS 20 computer program. Research results shows that the teacher’s ability to apply literacy learning numeration got an average value of 2.8 which means done well. As for the learning outcomes of class IVB students were described from the results of the prerequisite test consisting of normality test results of 0.183, homogeneity test results of 0.698 and T-test results of 0.000. It can be concluded that there is an influence numeracy literacy learning on students’ mathematics learning outcomes of class IV students at UPT SPF SD Inpres Antang I Makassar.